CD4+ T cell dysregulation in major depressive disorder is associated with sleep disturbance - Gao, Yao; Lei, Zihan; Ren, Yifan; Zhan, Xianyan; Chen, Zirong; Guo, Zuer; Zhou, Ziyang; Ma, Xiancang; Li, Pan (Frontiers in Psychiatry, 2026)
BackgroundEmerging evidence supports the role of immune-mediated neuroinflammatory processes and disrupted sleep patterns in elevating susceptibility to major depressive disorder (MDD). Sleep disturbances, a hallmark clinical feature of MDD, have further been linked to changes in lymphocyte profiles. Nevertheless, the potential relationship between sleep disturbance and lymphocyte subpopulations characteristic in patients with MDD remains underexplored.MethodsIn this study, flow cytometry was used to measure the proportion of peripheral blood CD4+ T-helper cells in 63 patients with MDD and 60 age- and sex-matched healthy controls (HCs). The relationship between self-reported sleep disturbances and the proportion of these cells was evaluated using Pearson’s correlation coefficient.ResultsBaseline scores on the Hamilton Depression Rating Scale (HAMD) and Self-Rating Depression Scale (SDS) in patients with MDD were significantly higher than those in HCs. Regardless of antidepressant medication use, patients with MDD exhibited elevated proportions of CD4+ regulatory T cells (Tregs), IFN-γ+-Tregs, IL-4+-Tregs and Th1 (IFN-γ+-CD4+ T) cells compared to HCs. Furthermore, the Pittsburgh Sleep Quality Index (PSQI) scores in patients with MDD showed a positive correlation with CD4+ T cell frequency. Notably, MDD patients with self-reported sleep disturbance had a higher CD4+ T cell percentage than those without such disturbance.ConclusionsOur findings demonstrate that patients with MDD comorbid with sleep disturbances exhibit elevated proportions of CD4+ T cells compared to those without such disturbance. These results suggest that targeted interventions addressing sleep disruption may contribute to restoring CD4+ T cell homeostasis, potentially offering a novel therapeutic strategy for MDD management.